THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY, ENVIRONMENTAL PERFORMANCE AND COMPANY SIZE ON PROFITABILITY IN COAL MINING COMPANIES LISTED ON THE IDX IN THE 2020-2024 PERIOD - Fibriyanti, Yenni Vera; Rachmawati, Evi (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
This study aims to analyze the partial and simultaneous influence of Corporate Social Responsibility (CSR), Environmental Performance, and company size on profitability in mining companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period. The study sample consisted of 21 companies observed over a three-year period, resulting in a total of 105 observations. This study uses a quantitative approach with panel data regression analysis to examine the relationship between the independent variables and the dependent variable. The results of the study show that CSR has a significant positive effect on company profitability, indicating that companies that are more active in implementing social responsibility tend to have better financial performance. Good environmental performance has been shown to increase company profitability, indicating that the implementation of environmentally friendly practices can bring financial benefits through improved corporate image. Large company size allows companies to enjoy economies of scale, have higher bargaining power, and are more stable in facing external risks. Overall, this study provides empirical evidence that CSR, Environmental Performance and company size have an important role in increasing company profitability in the mining sector, as well as contributing to economic and environmental sustainability.